2019
DOI: 10.1038/s41371-019-0208-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of snoring patients with primary aldosteronism and obstructive sleep apnea–hypopnea syndrome

Abstract: The 2016 guideline on the work-up of primary aldosteronism recommended that patients with obstructive sleep apnea–hypopnea syndrome (OSAS) be screened. This study aimed to identify the clinical characteristics of snoring patients with primary aldosteronism (PA) complicated by OSAS. Sixty-eight self-reported or witnessed snoring patients and 609 non-snoring patients diagnosed with PA between 2010 and 2015 were recruited in this retrospective study. Compared to non-snoring patients, snoring patients had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In the patient group, as expected, the sleep apnea variables were highly correlated, with a high AHI and high BMI predicting a low SpO 2 and increasing age predicting lower sleepiness, SpO 2, and lower subjective nasal obstruction. These findings are in line with previous findings of a positive correlation between AHI and BMI [29] and a negative correlation between BMI and the lowest SpO 2 [30], between AHI and SpO 2 min [31], and between age and ESS scores [32].…”
Section: Discussionsupporting
confidence: 93%
“…In the patient group, as expected, the sleep apnea variables were highly correlated, with a high AHI and high BMI predicting a low SpO 2 and increasing age predicting lower sleepiness, SpO 2, and lower subjective nasal obstruction. These findings are in line with previous findings of a positive correlation between AHI and BMI [29] and a negative correlation between BMI and the lowest SpO 2 [30], between AHI and SpO 2 min [31], and between age and ESS scores [32].…”
Section: Discussionsupporting
confidence: 93%
“…A total of 17 studies examined PAC (Barceló et al, 2014 ; Cho et al, 2015 ; di Murro et al, 2010 ; Follenius et al, 1991 ; Gjorup et al, 2007 ; Ishikawa et al, 2008 ; Ke et al, 2017 ; Li et al, 2019 ; Lykouras et al, 2015 ; Maillard et al, 1997 ; Moller et al, 2003 ; Muxfeldt et al, 2014 ; Nishijima et al, 2014 ; Svatikova et al, 2009 ; Thunstrom et al, 2016 ; Zalucky et al, 2015 ; Zhang et al, 2019 ), whereas seven articles reported AngII levels (Gjorup et al, 2007 ; Ishikawa et al, 2008 ; Moller et al, 2003 ; Takahashi et al, 2005 ; Wang et al, 2011 ; Zalucky et al, 2015 ; Zhang et al, 2019 ) compared with people without OSA. Seventeen studies compared blood pressure between people with OSA and those without (Barceló et al, 2014 ; Cho et al, 2015 ; di Murro et al, 2010 ; Florczak et al, 2013 ; Gjorup et al, 2007 ; Ishikawa et al, 2008 ; Ke et al, 2017 ; Li et al, 2019 ; Lykouras et al, 2015 ; Moller et al, 2003 ; Muxfeldt et al, 2014 ; Nishijima et al, 2014 ; Svatikova et al, 2009 ; Thunstrom et al, 2016 ; Wang et al, 2011 ; Zalucky et al, 2015 ; Zhang et al, 2019 ). Twelve studies were conducted in Western population and eight were conducted in Asian population, mainly the Japanese and Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies compared blood pressure between people with OSA and those without (Barcel o et al, 2014;Cho et al, 2015;di Murro et al, 2010;Florczak et al, 2013;Gjorup et al, 2007;Ishikawa et al, 2008;Ke et al, 2017;Li et al, 2019;Lykouras et al, 2015;Moller et al, 2003; Sub-analysis was performed to see if the parameters of RAAS remained significantly elevated among patients without resistant hypertension. After removal of these studies (di Murro et al, 2010;Ke et al, 2017;Li et al, 2019;Muxfeldt et al, 2014), PAC (p = 0.0199), SBP (p = 0.0027) and DBP (p = 0.0019) remained significantly elevated among patients with OSA. ARR level became significantly higher among those with OSA compared with the non-OSA group (p < 0.001), whereas PRA level became non-significantly different between groups (p = 0.0657) with removal of studies of patients with resistant hypertension.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, an early retrospective study reported that among 3,428 hypertensive patients, patients with hyperaldosteronism had a higher prevalence of sleep apnea than those without hyperaldosteronism (18% vs. 9%), despite a lack of confirmation of PA ( 16 ). It should be mentioned that a much lower prevalence of OSA (10%) in a retrospective study including 677 PA patients may be attributed to the fact that polysomnography (PSG) was only conducted in those with snoring, which resulted in the underestimation of the actual prevalence of OSA in PA ( 12 ).…”
Section: Coexistence Of Pa and Osamentioning
confidence: 99%